High ionic conductivity of Lu2O3–TiO2 co-doped Bi2O3 ceramics - Zeyang Luo; Huan Wang; Yuxin Ma; Guodong Zhang; Duanting Yan; Xinyu Bai; Dejun Wang; Runru Liu (Materials Research Express, 2021)
In this study, a promising electrolyte material Bi _0.76 Lu _0.16 Ti _0.08 O _1.5+ _δ (abbreviated as ‘8T16LSB’) with high oxygen ion conductivity was obtained by co-doping with Lu _2 O _3 and TiO _2 into Bi _2 O _3 . The phase composition, microstructure, and conductivity of TLSB ceramics were respectively investigated by x-ray diffraction, scanning electron microscopy (SEM), and electrochemical impedance spectroscopy (EIS). XRD results exhibited that the sintered TLSB ceramics with an unchanged total doping concentration of 24 mol.% existed as a cubic fluorite structure. SEM results showed that the TLSB pellets were relatively dense. The relationship between temperature and conductivity showed that the 8T16LSB ceramic exhibited the highest conductivity of 0.56 S cm ^−1 at 700 °C, which was higher than the value of 0.37 S cm ^−1 for the representative single-doping Er _0.4 Bi _1.6 O _3 (abbreviated as ‘20ESB’). The results certified that the electrochemical performance of Bi _2 O _3 was promoted by the co-dopant of Lu ^3+ and Ti ^4+ .